Beatrix Potter's Contribution to Children's Literature between Reality and Narrative Representation - Chiara Lepri (Firenze University Press, 2020)
The paper intends to deepen the artistic and authorial contribution of the British illustrator Beatrix Potter not only to works, poetics and stylistic elements, but also, in parallel, to the existential level since, over the years and in the socio-cultural context in which she lived, she embodied a model of an independent woman, able to emerge from the conflict between social norms and aspirations and to become an emblem of a culture of resistance and otherness that finds its natural and happy expression and continuation in the wide and varied sphere of children's literature. Therefore, in conclusion, the key elements are enucleated, which are open and can be deepened, aimed at underlining, in the author's human and literary testimony, the character of originality and the innovative scope of the work.